Indicators as a Tool for Assessing the Level of Sustainable Urban Freight Logistics - Bartuška, Ladislav; Hanzl, Jiří; Kampf, Rudolf; Brlek, Predrag (Promet - Traffic&Transportation, 2023)
Urban transport system planning has been moving towards sustainability in recent years, and the concept of urban freight logistics is an integral part of this planning. Urban freight logistics involves many stakeholders that participate in its operation and should be considered in the system planning process. The paper presents one of the approaches to the methodology for the selection of key indicators suitable for the evaluation and monitoring of a sustainable system of urban freight logistics in such a way that it reflects as much as possible the needs of all involved stakeholders. This is done by applying the selected method of multi-criteria analysis with the involvement of various urban freight logistics stakeholders. Based on the proposed methodology, the paper defines significant indicators that can be considered for further evaluation of the level of a sustainable urban freight logistics system. In addition to the possibilities of further development of this methodology, the application of determined significant indicators for calculating the proposed index of sustainable urban freight logistics is discussed. The proposed procedure can be implemented in the preparatory steps in the framework of the creation of sustainable urban logistics plans (SULPs).